Camouflage strategies interfere differently with observer search images - Troscianko, Jolyon (Proc Biol Sci, 2018)
Numerous animals rely on camouflage for defence. Substantial past work has identified the presence of multiple strategies for concealment, and tested the mechanisms underpinning how they work. These include background matching, D-RUP coloration to destroy target edges, and distractive markings that may divert attention from key target features. Despite considerable progress, work has focused on how camouflage types prevent initial detection by naive observers. However, predators will often encounter multiple targets over time, providing the opportunity to learn or focus attention through search images. At present, we know almost nothing about how camouflage types facilitate or hinder predator performance over repeated encounters. Here, we use experiments with human subjects searching for targets on touch screens with different camouflage strategies, and control the experience that subjects have with target types. We show that different camouflage strategies affect how subjects improve in detecting targets with repeated encounters, and how performance in detection of one camouflage type depends on experience of other strategies. In particular, disruptive coloration is effective at preventing improvements in camouflage breaking during search image formation, and experience with one camouflage type (distraction) can decrease the ability of subjects to switch to and from search images for new camouflage types (disruption). Our study is, to our knowledge, the first to show how the success of camouflage strategies depends on how they prevent initial and successive detection, and on predator experience of other strategies. This has implications for the evolution of prey phenotypes, how we assess the efficacy of defences, and predator–prey dynamics.